Corrosion behavior of the 3 wt.% Ni weathering steel with replacing 1 wt.% Cr in the simulated tropical marine atmospheric environment. (April 2023) - Zhang, Bo; Liu, Wei; Sun, Yipu; Yang, Weijian; Chen, Longjun; Xie, Jiaqi; Li, Wenqi
Abstract: The effect of using 1 wt% Cr instead of 1 wt% Ni on the corrosion behavior of 3 wt% Ni steel in the simulated tropical marine atmospheric environment is studied. The results show that replacing part of Ni in 3 wt% Ni steel with Cr can effectively promote the conversion of γ-FeOOH to α-FeOOH during the early stages of corrosion, which facilitates the densification of the rust layer to prevent the intrusion of corrosive media. As corrosion test periods and Cl − concentration increased, the hydrolysis effect of Cr causes local acidification leading to corrosion pits develop deeper and severe local corrosion, while destroying the protective nature of the rust layer and exhibiting strong electrochemical reaction activity. Highlights: The effects of using Cr instead of part of Ni on the corrosion behavior of Ni-steel is studied. More α-FeOOH are formed during the early stages of corrosion. The hydrolysis effect of Cr gradually increases electrochemical activity of Ni–steel.